A Provocative Perspective on Population Aging and Old-Age Financial Protection - Robert Holzmann (Institute for the Study of Labor (IZA), 2013)
Population aging is typically associated with economic challenges for productivity and financial threats for the old-age financial protection system of a country. This paper takes an optimistic position and outlines key ingredients to make it a successful experience. Yet to turn this challenge into an opportunity requires a significant change in a society's mindset and policies, such as recognizing that population aging and increased life expectancy are quite likely the biggest challenge to mankind in recorded history. This calls for a review and revision of societal institutions, from the likely oldest one marriage to one of the youngest retirement income schemes. Mere tinkering at the margin of existing retirement income programs will be neither sufficient nor helpful. To develop the arguments, the paper reviews and proposes changes to the measurement of population aging globally and for East Asian countries; outlines critical policy paths to address population aging successfully; analyzes the implications of population aging for the selection of an old-age financial protection system; and offers guidance to this end.
Keywords: H55; J11; J14; J26; 330; NDC; life expectancy; measuring population aging; happy aging; FDC